2019
DOI: 10.1007/s40520-019-01251-1
|View full text |Cite
|
Sign up to set email alerts
|

Mindwandering propensity modulates episodic memory consolidation

Abstract: Research into strategies that can combat episodic memory decline in healthy older adults has gained widespread attention over the years. Evidence suggests that a short period of rest immediately after learning can enhance memory consolidation, as compared to engaging in cognitive tasks. However, a recent study in younger adults has shown that post-encoding engagement in a working memory task leads to the same degree of memory consolidation as from post-encoding rest. Here, we tested whether this finding can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Indeed, Craig and colleagues (2016) demonstrated that wakeful rest exhibited beneficial effects on cognitive map accuracy for both younger and older adults and Alber et al (2014) showed that wakeful rest benefited both amnestic patients and healthy controls on prose 1 One might argue that wakeful rest simply provides less interference than the distractor task. However, several pieces of literature have indicated that distractor tasks that do not engage episodic memory processes also allow for consolidation (see Varma et al, 2018;Varma et al, 2019).…”
Section: Memory Consolidation Wakeful Rest and Mind-wanderingmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, Craig and colleagues (2016) demonstrated that wakeful rest exhibited beneficial effects on cognitive map accuracy for both younger and older adults and Alber et al (2014) showed that wakeful rest benefited both amnestic patients and healthy controls on prose 1 One might argue that wakeful rest simply provides less interference than the distractor task. However, several pieces of literature have indicated that distractor tasks that do not engage episodic memory processes also allow for consolidation (see Varma et al, 2018;Varma et al, 2019).…”
Section: Memory Consolidation Wakeful Rest and Mind-wanderingmentioning
confidence: 99%
“…The results of this study suggest that wakeful rest may benefit memory via a consolidation process supported by slow, oscillatory EEG activity and increased MW related to offline memory replay 2 . However, given the substantial variability in individuals' MW contents during wakeful rest periods (see Brokaw et al, 2016;Varma et al, 2019), one might wonder whether thoughts could be directly influenced to enhance memory reactivation during wakeful rest periods. Indeed, several targeted memory reactivation studies have investigated this issue.…”
Section: Memory Consolidation Wakeful Rest and Mind-wanderingmentioning
confidence: 99%
See 3 more Smart Citations